STRATEGI PEMUNGUTAN PAJAK BUMI DAN BANGUNAN DALAM UPAYA PENINGKATAN PENDAPATAN ASLI DAERAH KABUPATEN PANDEGLANG - Pertiwi, Sari Putri; Oktaviani, Rini (Gapenas Publisher, 2023)
Indonesia is a developing country with a wide range of revenues, including tax collection from state and local (local) taxes. One of the taxes that is the source of our country's income is the Land and Building Tax (PBB). The purpose of the study is to find out the procedures in collecting UN are according to standards or not, knowing good strategies in collecting Land and Building Tax so that there is an increase in PAD and knowing what factors are obstacles or obstacles in collecting Land and Building Tax. The research used qualitative approach method. Types of analytical descriptive research. The results of the study are internal factors and external factors that affect UN voting. strategies undertaken to increase UN voting. The procedure used in the UN vote. UN collection payment procedure. The development of the realization of Regional Original Revenue revenue of Pandeglang Regency in 2018-2022 has decreased. The conclusion is that internal factors that affect UN voting are insufficient human resources, inadequate facilities and infrastructure and budget. External factors that affect UN voting are in the field of technology, namely weak in IT. UN voting procedures are registration, data collection, assessment, determination, acceptance, billing, service and objection. The procedure for paying Land and Building Tax can be offline and online. The strategy used is to disable SPPT, sanction and hold Anev socialization (Analysis and Evaluation). The development of PAD revenue realization in Pandeglang Regency in 2018-2022 has decreased